Effects of Social Investment Programme (N-Power) on Standard of Living of Business Education Graduates in Kano State - Saleh Muhammad Aminu (European Scientific Journal, ESJ, 2019)
This paper focuses on the effects of Social Investment Programme (NPower) on standard of living of business education graduates in Kano State, Nigeria. Social Investment aims at granting youths the power to perform their duties and create change. It has to do with teaching them about their ability to control their lives and change society to inculcate a sense of value. N-Power is one of the five Social Investment Programmes of the Federal Government of Nigeria under President Muhammadu Buhari led administration. Two research questions guided the study with one corresponding hypothesis tested at 0.05 level of significance. The descriptive survey research design was adopted in the study. The population was made up of 26 and 30 volunteers from Nassarawa and Fagge LGAs respectively, and 28 supervisors. A structured questionnaire titled N-power Questionnaire (NPQ) was developed by the researcher and was structured into 4 rating scale. Percentages, mean, and standard deviation were used to answer the research questions and one null hypothesis. The findings revealed that N-power SIP had significant effects in improving the standard of living of business education graduates in Kano State. Based on the findings, a major recommendation highlighted was that States government should commit funds to social investment programmes since it helps to improve the standard of living of volunteers.